Participatory assessment of management and biosecurity practices of smallholder pig farms in North East India - Singh, Mahak; Pongenere, Nungshitula; Mollier, R. T.; Patton, R. N.; Yadav, Rekha; Katiyar, Rahul; Jaiswal, Priyanka; Bhattacharjee, M.; Kalita, H.; Mishra, V. K. (Frontiers in Veterinary Science, 2023)
The present study was aimed at describing the pig production system, farm management, pig movement, and existing biosecurity level of smallholders' pig production system in North East India. A cross-sectional survey of 1,000 pig producers in four districts (two urban and two rural) in core pig-producing regions of India, where ASF occurrence had been reported, was conducted. The mean pig population was significantly (p < 0.05) higher in urban districts. In urban districts, most of the pig houses were isolated but located on the roadside, while in rural districts, commune pig houses along the roadside were more common. The majority of the respondent purchased (91%) or sold (60%) the pigs during the past 12 months. Swill feeding was common in the entire study area. The majority of the respondent (80%) in rural districts were unaware of ASF. Significant pig trade of live pigs and pork products was observed in the urban district. In the case of on-farm biosecurity measures, only 6.9% of respondents had fencing for the pig farm, 99.3% did not have provision for a footbath, and only 17.2% of the respondents restricted visitors' access to the pig farm. The study revealed that the pig production system is dominated by smallholding units with a frequent introduction or exit of pigs along with poor on-farm biosecurity measures. With the current level of farm management and biosecurity practices, smallholder pig farmers are at an increased risk of ASF and other contagious diseases.